Information consulting : Guide to good practice - Wormell, Irene (Chandos information professional series., 2011)
This book presents a closer look at what makes information consultants successful and how they develop a productive relationship with their clients. While most of the books on this subject area are providing the experiences of information consulting veterans on 'how do you really do it?', the aim of this book is focused on exploring the nature of information management consulting. This incluses the task of the advice-and-guidance variety, such as helping clients to analyze and solve problems or to meet opportunities with the element of 'What should I do?'. The authors have used their extensive international and professional networks to take the challenge of letting the clients speak about their experiences and expectations in hiring information consultants.